Implementation of Renewable Energy Based Kemplang Drying House Technology in Talang Pangeran Ulu Village South Sumatra - Pratama Setiawan; Muhammad Jeri; Intan Cahyani Aprillianti; Jogi Imanuel Gultom; Maulia Musyahada (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to introduce renewable energy innovation through the development of a solar-powered kemplang drying house constructed with polycarbonate material in Talang Pangeran Ulu Village, South Sumatra. The initiative was designed to address the limitations of conventional sun drying, which is highly dependent on weather conditions and often results in prolonged drying times and inconsistent product quality. The implementation adopted a training and mentoring approach conducted in two stages. The first stage provided technical guidance on the design, construction, and operation of the solar-powered drying house. The second stage focused on enhancing participants’ capacity in digital marketing for product promotion through social media and e-commerce platforms. The activities applied a Participatory Rural Appraisal (PRA) approach, encouraging community involvement through discussions and practical demonstrations. Evaluation instruments included pre-test and post-test questionnaires, observation sheets to assess operational skills, and temperature measurements inside the drying house. The evaluation employed a one-group pre-test–post-test design, and the collected data were analyzed using descriptive quantitative techniques to determine improvements in participants’ knowledge and skills. The results indicated that the drying house increased the internal temperature from approximately 32°C to 45–50°C, representing an increase of about 13–18°C. This condition accelerated moisture evaporation and improved drying efficiency. With daily production reaching 8,000–10,000 pieces, the kemplang exhibited more uniform dryness and better hygiene. Additionally, improved product quality and the adoption of digital